THE IMPACT OF SINGLE AMINO ACID MUTATIONS OR ALTERATIONS IN REGULATORY PROTEINS ON THE STEMNESS PROPERTIES OF CANCER CELLS - Sartika, Dewi; Laili, Irmatul; Utami, Sri (Journal of Stem Cell Research and Tissue Engineering, 2025)
Cancer stem cells (CSCs) represent a highly plastic subpopulation within tumors that drives tumor initiation, progression, metastasis, therapeutic resistance, and disease relapse. Although CSC traits were initially attributed to stable genetic hierarchies, growing evidence suggests that cancer stemness is a dynamic and reversible state regulated by precise molecular events at the protein level. This literature review aims to synthesize experimental evidence regarding the impact of single amino acid mutations and alterations in regulatory proteins on the stemness properties of cancer cells. A systematic literature search was conducted using PubMed and Google Scholar to identify original research articles published between 2020 and 2025 that examined protein-level mutations, post-translational modifications, epigenetic regulators, and chromatin remodeling factors in diverse cancer models. The reviewed studies consistently demonstrate that single amino acid substitutions in oncogenic, tumor suppressor, or regulatory proteins can profoundly affect protein conformation, stability, enzymatic activity, and protein–protein interactions. These alterations frequently result in sustained activation of key stemness-associated signaling pathways, including Wnt/β-catenin, Notch, Hedgehog, and STAT3, thereby enhancing self-renewal capacity, stem cell marker expression, tumor-initiating potential, and resistance to conventional therapies. In parallel, dysregulation of post-translational modification systems, such as phosphorylation, ubiquitination, acetylation, and methylation, promotes epigenetic reprogramming and reactivation of embryonic transcriptional programs that favor cellular plasticity. Moreover, protein-level alterations strengthen cancer cell interactions with the tumor microenvironment, increasing responsiveness to hypoxia, inflammatory signals, and metabolic stress. Collectively, these findings highlight protein-level regulation as a central determinant of cancer stem cell maintenance and plasticity, and suggest that effective therapeutic strategies should target aberrant protein stability, post-translational modification machinery, and stemness-related signaling networks to achieve durable clinical responses.